Manajemen Fisioterapi Dengan Short Wave Diathermy (SWD) Dan Terapi Latihan Pada Kasus Post Closed Reduction Shoulder E.C Fracture Tuberculum Majus Os. Humerus - Annisa Khalifatul Husna; Nungki Marliyani (Jurnal Anestesi, 2024)
Introduction: A humerus fracture is a fracture of the longest and largest bone in the superior extremity which is caused by direct or indirect impact or trauma and can cause damage to bone fragments, and affect the function of the musculoskeletal system which influences activity tolerance so that it can affect the sufferer's quality of life. Objective: Physiotherapy plays a role in reducing pain and overcoming impairment and activity limitation disorders so that it can restore a person's functional ability and quality of life. Method: The method used in this research is a case report where this research involves a woman with the initials Mrs. S, 73 years old, is one of the outpatients at the Medical Rehab Installation at Ngudi Waluyo Regional Hospital. Results: The physiotherapy intervention program in the form of SWD and exercise therapy was given 3 times to Mrs. S at Ngudi Waluyo Regional Hospital showed a decrease and increase in the range of motion of the shoulder joint.